Coastal aggregation of marine turtles in waters of the South Pacific of Costa Rica. - Venegas-Li, Rubén (2015)
The southern Pacific coast of Costa Rica has been identified as an important place for the reproduction of four species of marine turtles. This presence, coupled with threats to the survival of the species, has encouraged the establishment of conservation initiatives and the study of these animals in the region, especially in nesting areas. Nonetheless, information on their presence in the water (where they spend most of their life) is scarce. For this reason, this study analyses data from a three years of a marine turtle monitoring program by Fundación Keto in the area between the Marino Ballena National Park and the Caño Island Biological Reserve, and presents the temporal and spatial distribution of the observed individuals. During this period, a total of 447 turtle (sightings per sampling effort=0.36 individuals-hr-1), of three different species were observed: Lepidochelys olivacea, Chelonia Mydas, and Eretmochelys imbricata. Sightings have been recorded during all months of the year, with L. olivacea as the species most commonly observed, especially outside of protected areas; this species presented a clear mating period in the months of July and August. E. imbricata was the species observed closer to the shore, and at a shallower site, possibly indicating an important foraging area for juvenile individuals. This is the first study to address the consistent and permanent presence of three species of marine turtles in the waters off the coast of Cantón de Osa in the southern Pacific coast of Costa Rica.